Analyzing listening awareness development through strategies based on basic instructions in a child with autism level 3 at a private school in the north of Guayaquil. - Córdova Guagua, Geraldine Antonella (2025)
This study investigates the development of listening awareness through strategies based on instructions for an 11-year-old child diagnosed with Level 3 autism in a private school in northern Guayaquil. The present research employed a qualitative methodology and a descriptive approach, utilizing classroom observations and teacher interviews as data gathering tools. Findings indicate that multisensory approaches and individualized instruction play a crucial role in delivering a positive learning experience, as well as teacher training and adaptability. The use of strategies like Total Physical Response (TPR) and Picture Exchange Communication System are helpful tools to teach English to students on the autistic spectrum. By offering practical recommendations, this research contributes to the application of inclusive education practices that promote the integration of students with autism and their academic success. The results highlight the necessity of implementing strategies that align with the abilities of the learners fostering a more accessible and supportive educational environment.